Relación entre las transferencias del programa juntos y el nivel de pobreza monetaria en la provincia de Maynas 2016 – 2023 - Perea Churay, Jose Smith (2025)
The main objective of this research was to analyze the relationship between transfers from the Juntos Program and the level of monetary poverty in the province of Maynas during the period 2016-2023. Using a quantitative approach, the behavior of both variables was evaluated at the general, urban, and rural levels, using descriptive and inferential analyses. The results showed a inverse and statistically significant relationship between the amount of program transfers and the level of monetary poverty in Maynas, both at the aggregate level and by geographic area. However, the magnitude of the effect is moderate in urban areas and weak in rural areas, indicating limitations in the program's capacity to generate sustained poverty reduction. Likewise, disparities in the territorial distribution of resources were identified, with a concentration in districts such as San Juan Bautista and insufficient coverage in others with a high incidence of poverty, such as Punchana and Belén. In conclusion, although the Juntos Program contributes to alleviating monetary poverty, its structural impact remains limited.